Elucidating the chemistry of particulate and chlorinated nitrates in the troposphere through method development, and chamber and field studies - Garner, Natasha Michelle (Science, 2020)
This thesis explores the chemistry of chlorinated and particulate nitrogen oxides in the troposphere which can impact the budgets of atmospheric oxidants and aerosol. Mixing ratios of nitryl chloride (ClNO2) were measured by chemical ionization mass spectrometry (CIMS) during the ORCA campaign in July 2015 on the west coast of Vancouver Island. Mean ClNO2 mixing ratios were small (< 10 pptv) with a maximum of 46 pptv, in part due to low precursor concentrations, i.e., of nitrogen dioxide (NO2) and ozone, and large nitrate radical sinks, e.g., titration by monoterpenes. Concentrations of ClNO2 were enhanced in air masses with elevated NO2 concentrations that had resided over the ocean, demonstrating the potential of ClNO2 to affect radical budgets in remote environments. The potential loss of ClNO2 by uptake on inorganic and secondary organic aerosol (SOA) was investigated in a newly constructed smog chamber. Uptake probabilities (γ) were determined by box modeling constrained to measured ClNO2 mixing ratios and SMPS derived aerosol surface area. An upper limit of γ< 4x10-4 was determined for (NH4)2SO4 and NH4HSO4 aerosol, but larger values were needed for monoterpene derived SOA, i.e., γ=(8+/-2)x10-4. Uptake of ClNO2 on SOA reduces its lifetime and impact on nitrogen oxide and chlorine budgets downwind of coastal areas where marine and continental air masses combine. A method to quantify NH4NO3 and NaNO3 aerosol by thermal dissociation cavity ring-down spectroscopy (TD-CRDS) was developed. At inlet temperatures of 540 °C and 620 °C, respectively, scatter plots of SMPS volume distribution data and TD-CRDS mixing ratios correlated (r2>0.9) with unity slopes in laboratory experiments. Sample ambient air measurements in Calgary, AB in August 2018 showed the presence of particulate organic nitrates at inlet temperatures < 350 °C (consistent with smog chamber experiments with limonene SOA) and of inorganic nitrate aerosol, demonstrating the potential of TD-CRDS for ambient particulate measurements.